Voltage-Mode Four-Phase Sinusoidal Generator and Its Useful Extensions - Sudhanshu Maheshwari (Active and Passive Electronic Components)
This paper introduces a new voltage-mode second-order sinusoidal generator circuit with four active elements and six passive elements, including grounded capacitors. The frequency and condition of oscillation can be independently controlled. The effect of active element’s nonidealities and parasitic effects is also studied; the proposed topology is good in absorbing several parasitic elements involved with the active elements. The circuit is advantageous for generating high frequency signals which is demonstrated for 25 MHz outputs. Several circuit extensions are also given which makes the new proposal useful for real circuit adoption. The proposed theory is validated through simulation results.